The restructuring of schooling in England: The responses of well-positioned headteachers. (May 2014) - Coldron, John; Crawford, Megan; Jones, Steve; Simkins, Tim
Research to date about the English government's policy to make schools independent of local authorities (LAs) has looked at the 'macro' level of national policy and at the 'micro' level of the institution. The study of which this article is a part, explores changes at the 'meso' level – the locality. The article analyses interviews in three LAs with 15 headteachers whose schools were well positioned locally. We sought to understand how and why they responded to the changing policy environment. We applied Bourdieu's concepts of forms of capital to model the relationships between schools and to ground explanations of their responses as positioning themselves in the local field. The article develops this general approach by identifying the varieties of capital available and actually possessed. The most important was categorization as a result of the inspection process. Many of the headteachers felt impelled to lead their schools into various associations with other schools. Some individuals were becoming notably more powerful in their competition arenas. The power of these elite schools to further accumulate advantage and the withdrawal of the LA role as an arbiter of conflict between schools in the interests of the whole community are discussed.